The surgical management and prevention of laparoscopic cholecystectomy associated bile duct injuries - Lindemann, Jessica Danielle (Division of General Surgery, 2021)
Laparoscopic cholecystectomy (LC) is considered the gold standard in the surgical management of gallstone disease and is one of the most commonly performed general surgery operations worldwide. Bile duct injury (BDI) in LC remains a feared complication as it is associated with significant morbidity, prolonged hospital stay, increased costs, and reduced quality of life for patients, as well as the risk of litigation for the injuring surgeon. The initial incidence of BDI after the introduction of LC was reported to be between 0.4 and 0.8%, which was higher than the estimated 0.2% reported during the open cholecystectomy era. However, recent reports from the United States and Europe suggest a return to open cholecystectomy rates. Despite being a frequently performed operation in both the private and public health sectors in South Africa, there is a paucity of data on the incidence of BDI. In the only study to date reporting the frequency of BDI in South Africa, a single centre incidence of 1.2% was documented over an 18-month period, which is significantly higher than previous reports. No data have been published on the implications of BDI for patients treated within the South African healthcare system. This thesis describes the surgical management of BDI at an academic referral centre over a thirty-year period. Potential factors influencing treatment and patient outcome after BDI are investigated. These include the influence of geographic distance from referral centre on the timing of referral and repair, and subsequent long-term patient outcomes. The influence of dual healthcare sectors (public vs. private) on access to diagnostic and interventional modalities, and eventual outcome is also investigated, and the evolution in the management of BDIs over the three studied decades is documented. Factors associated with loss of patency following surgical repair of LC-BDIs are also determined. Based on the findings of this detailed review of the management and outcomes of LC-BDIs, a treatment algorithm for management in resource-constrained environments is proposed. Establishing the optimal management of LC-BDIs in a developing country healthcare setting is important but does not address the source of the problem. In an effort to make LC-BDI a near-never event, a standardized method of performing, documenting and monitoring the quality of LC was developed and implemented for all LCs performed in the Cape Metro West health district. Prospective data collection is scheduled to continue to the end of 2020; however, an interim analysis is presented. A previously published scoring system for assessing quality of the critical view of safety achieved during LC, a critical component of a safe LC, is applied and validated in a large cohort of LC patients. A prospective database was created for data capture along with a Standard Operating Procedure, both designed with the goal of expanding the intervention and database nationally. The studies reported in this thesis make a substantial contribution to the literature and will have a beneficial impact on patient care in two important ways. Firstly, the management of BDI in South Africa is described and a treatment algorithm for resource-constrained environments is proposed, based on local experience. Secondly, a change of practice was implemented and a LC database was established with the possibility of expanding the effort to the national level. Locally, the change in practice has thus far resulted in identification of areas of improvement to limit BDI and increased knowledge about the appropriate steps to take to avoid causing a LC-BDI.